Eukaryotic Translation Initiation Factor 3 Subunit B Is a Promoter in the Development and Progression of Pancreatic Cancer - Ren, Haoyuan; Mai, Gang; Liu, Yong; Xiang, Rongchao; Yang, Chong; Su, Wenjie (Frontiers in Oncology, 2021)
Background: Pancreatic cancer (PC) is a malignant tumor with hidden incidence, high degree of malignancy, rapid disease progression and poor prognosis. Eukaryotic translation initiation factor 3 subunit B (EIF3B) is necessary for tumor growth, which is an alternative therapeutic target for many cancers. However, little is known about the relationship between EIF3B and PC. Methods: The expression of EIF3B in PC was detected by immunohistochemistry. EIF3B knockdown cell models were constructed by lentivirus infection. The MTT assay, the wound-healing assay, the transwell assay, the flow cytometry and the Human Apoptosis Antibody Array was used to detect the effects of EIF3B knockdown on cell proliferation, cell migration, cell apoptosis and cell cycle in vitro. Also, the effects of EIF3B knockdown on the tumor growth of PC were determined in vivo. Results: This study showed that the expression level of EIF3B was significantly up-regulated in PC tumor tissues and associated with pathological grade. In vitro, EIF3B knockdown inhibited the PC cell proliferation and migration, and the apoptosis levels were obviously promoted by regulating apoptosis-related proteins including Bcl-2, HSP27, HSP60, Survivin, sTNF-R2, TNF-α, TNF-β, TRAILR-3, TRAILR-4 and XIAP. Furthermore, the tumor growth of PC was inhibited after the knockdown of EIF3B in vivo. Conclusion: EIF3B was up-regulated in PC and was a promoter in the development and progression of PC, which could be considered as a therapeutic target for the treatment of PC.